Methodology for the measurement and estimation of pedestrian and cycle traffic at level crossings - Tanel Jairus; Stanislav Metlitski; Mihkel Kask; Kati Kõrbe (Proceedings of the Estonian Academy of Sciences)
Urban and suburban level crossings are critical intersection points between rail and pedestrian infrastructure, requiring careful monitoring and analysis of traffic patterns for safety and planning purposes. This paper presents a comprehensive methodology for measuring and estimating pedestrian and cycle traffic at urban and suburban level crossings. A dual-component system is introduced that considers separately regular crossing users and rail transport passengers, acknowledging their distinct temporal patterns. Three distinct temporal patterns were identified for both pedestrian movement and rail passenger flows through analysis of fixed counter data and passenger statistics, while a singular pattern was determined for cyclists. The methodology was validated at 14 railway crossings, establishing minimum requirements for measurement duration and optimal timing. The results indicate that counting periods of at least 24 hours are required, with optimal accuracy achieved during the spring and autumn months. This approach provides optimal resource usage for achieving adequate accuracy. Data collection and estimation supported by this framework will provide the grounds for evidence-based decision-making in railway crossing infrastructure planning and safety assessment.